2011
DOI: 10.1007/s10735-011-9364-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of curcumin on intestinal oxidative stress, cell proliferation and apoptosis after ischemia/reperfusion injury in rats

Abstract: The aim of this study was to demonstrate the role of curcumin on oxidative stress, cell proliferation and apoptosis in the rat intestinal mucosa after ischemia/reperfusion (I/R). A total of 30 male Wistar albino rats were divided into three groups: sham, I/R and I/R+ curcumin; each group contain 10 animals. Sham group animals underwent laparotomy without I/R injury. After I/R groups animals underwent laparotomy, 1 h of superior mesenteric artery ligation were followed by 1 h of reperfusion. In the curcumin gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 34 publications
8
30
0
1
Order By: Relevance
“…It is generally accepted that ischemic heart injury is a pathological process, which will cause extensive death of cells (Yucel et al, 2011). Furthermore, ischemic heart diseases can produce apoptosis, and the apoptosis might be related to both extrinsic and intrinsic apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that ischemic heart injury is a pathological process, which will cause extensive death of cells (Yucel et al, 2011). Furthermore, ischemic heart diseases can produce apoptosis, and the apoptosis might be related to both extrinsic and intrinsic apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that curcumin attenuates I/R injury in various organs in vivo and in vitro, including the intestines, retina, liver and renal system, through anti-oxidative stress and anti-apoptotic mechanisms (20)(21)(22)(23) through the attenuation of oxidative stress and mitochondrial dysfunction. However, the beneficial effects of curcumin on the extent of apoptosis and autophagy in myocardial I/R, and their potential mechanisms, remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, a herbal medicine with powerful antioxidant, 17 has been widely used as a therapeutic agent for a variety of diseases from cancer to Alzheimer's to infectious diseases, 18 especially for I/R related injury in different tissues. 6,[19][20][21] For example, just recently, Avci et al…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that administration of curcumin could ameliorate I/R injury in rat kidney, myocardium, and nervous tissue. [6][7][8] However, to the best of our knowledge, little is known about its effect on I/R injured spinal cord. In this study, we examined its neuro-protective effect and potential mechanism in a rabbit model with I/R injury.…”
Section: Introductionmentioning
confidence: 99%